Autonomous Expenditures Versus Money Supply: An Application of Dynamic Multipliers - Kmenta, J.; Smith, P. E. (The Review of Economics and Statistics, 1973)
PpT HE purpose of this paper is to test empirically two propositions which have been closely, although not exclusively, associated with Milton Friedman in recent years. The first is the hypothesis that changes in monetary or fiscal policy variables are frequently ineffective in stabilizing some target variable because they are poorly timed.1 The second hypothesis, which was presented by Friedman and Meiselman (1963), is that the money supply is a more important determinant of aggregate demand than autonomous expenditures.2 We test these hypotheses by considering the effects of changes in fiscal and monetary variables upon the movements in gross national product within the framework of a small, short-run econometric model of the United States economy. In our model both money supply and government expenditure are regarded as autonomous manipulative policy instruments. A special feature of the study is a quarter-by-quarter investigation of the effects of changes in each of the two policy variables upon the movement of GNP. The period of investigation dates from the end of the Korean War (1954-I) to the beginning of serious military involvement in Vietnam (1963-IV). The plan of the paper is as follows: In section II we specify and estimate the structural equations of the model. Section III is concerned with a dynamic analysis of the system. Here we derive our estimates of the dynamic multipliers and examine the system for stability. In section IV we utilize the preceding results to determine the relative importance of each of the two policy variables during the sample period. Simplified criteria are suggested and applied for evaluating the actual operation and relative effectiveness of the two types of policy. The final section contains a summary of the main results and some concluding remarks.